Transcriptomic analysis reveals candidate genes associated with anther development in Lilium Oriental Hybrid ‘Siberia’ - Dong, Tingting; Wang, Lixuan; Wang, Rui; Yang, Xi; Jia, Wenjie; Yi, Mingfang; Zhou, Xiaofeng; He, Junna (Frontiers in Plant Science, 2023)
Lily (Lilium spp. and hybrids) is an important cut flower crop worldwide, Lily flowers have large anthers, which release a large amount of pollen that stains the tepals or clothing, and thus can affect the commercial value of cut flowers. In this study, lily Oriental ‘Siberia’ was used to investigate the regulatory mechanism of lily anther development, which may provide information to prevent pollen pollution in the future. Based on the flower bud length, anther length and color and anatomical observations, lily anther development was categorized into five stages: green (G), green-to-yellow 1 (GY1), green-to-yellow 2 (GY2), yellow (Y) and purple (P).Total RNA was extracted from anthers at each stage for transcriptomic analysis. A total of 268.92 Gb clean reads were generated and 81,287 unigenes were assembled and annotated. The number of differentially expressed genes (DEGs) and unique genes were largest for the pairwise comparison between the G and GY1 stages. The G and P samples were clustered separately, whereas the GY1, GY2, and Y samples were clustered together, in scatter plots from a principal components analysis. Gene Ontology and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses of DEGs detected in the GY1, GY2, and Y stages, revealed that the pectin catabolic process, hormone levels, and phenylpropanoid biosynthesis were enriched. The DEGs associated with jasmonic acid biosynthesis and signaling were highly expressed at the early stages (G and GY1). Whereas the DEGs associated with phenylpropanoid biosynthesis were mainly expressed in the intermediated with stage(GY1, GY2 and Y). The DEGs involved in the pectin catabolic process were expressed at advanced stages (Y and P). Cucumber mosaic virus induced gene silencing of LoMYB21 and LoAMS caused a strongly inhibited anther dehiscence phenotype but without affecting the development of other floral organs. These results provide novel insights for for understanding the regulatory mechanism of anther development in lily and other plants.